ISLAMIC EDUCATION AND COMMUNITY EMPOWERMENT - M. Jamalun Nizar; Ervin Arifuddin; Yusuf Aspidin; Frendy Rahmansyah; Nihayatus Sholihah (International Conference on Humanity Education and Society (ICHES), 2023)
Islamic boarding schools in Indonesia put a lot of emphasis on the teachings that have been created by previous scholars known as the yellow book. Among these books there is a book of tool science, namely the science of nahwu, and the science of sharraf. In studying the science of nahwu sharraf in Islamic boarding schools, they usually use the Jurmiyah, Imrithi, and Nadzom Alfiyah books. But now, the Board of Tarbiyah Wa Ta'lim Madrasi (Batartama) at the Sidogiri Islamic Boarding School creating a book of nahwu sharraf teaching materials (Learning Materials for the Yellow Book: Al-Miftah Lil Ulum). This research activity is intended to find out how the planning activities, implementation activities and evaluation activities of the Al-Miftah Lil 'Ulum method at the Roudlotut Thohirin Sengon Pringgodani Islamic Boarding School, Bantur Malang. This study uses a descriptive qualitative approach. The results of this study indicate that: (1). The implementation of the Al-Miftah Lil 'Ulum method at the Roudlotut Thohirin Islamic Boarding School is seen from several factors including: (a) The increase in student learning outcomes seen from the mastery of the material. (b) increasing the ability to read the yellow book of students. (c) reading the book according to the rules. (2) Obstacles in the application of the Al-Miftah Lil 'Ulum method include: (a) Lack of adequate facilities and infrastructure. (b) lack of teaching staff.